STUDY OF POSTURAL ABNORMALITIES OF MALE STUDENTS OF SAHAND UNIVERSITY OF TECHNOLOGY - Hefzollesan Mehrdad; Ghalegir Sohrab (Physical Education of Students)
The present study has been accomplished in order to examine the prevalence of postural abnormalities of male students. The statistical community was the whole male students in the university. From this community 300 students within the ages range of 18 - 22 were selected randomly as the investigation subjects. Data were obtained by a questionnaire, podoscope, a digital camera (taking photos of the subjects from Anterior, Posterior and lateral views) and the software for corrective exercises provided by Iran ministry of education. After that the investigation was finished the abundance percentage was used to express the postural abnormalities percentage of the research subjects. The results show that cervical lordosis and flat foot are the most prevalent abnormalities with18.66 and 17.66 percent respectively, and torticollis and knee hyperextension have less prevalence in investigation subjects. The results show that among all of the participants in the investigation, 140 students (46.66 %) have no abnormalities, 160 students (53.34 %) have at least one, and 70 students (23.33 %) have more than one. From this study it is obvious that the prevalence of the postural abnormalities among the statistical subjects is high. Therefore the need to a serious program concerning the abnormalities, especially ordering corrective exercises and also preparing the way for students to have physical activities seems to be inevitable.